Pola Asuh Orang Tua yang Bekerja pada Masa Pandemi COVID-19 - Nurul Hidayati, Baiq; Romadonika, Fitri; Pratiwi Safitri, Rias; Layla Salfarina, Anna (Jurnal Ilmiah STIKES Yarsi Mataram, 2022)
During the COVID-19 pandemic, parents are required to spend more timeaccompanying their children's learning, taking part in their children's schoolwork, but also having to stay in their career or work (Nurina, 2020). Parenting isthe best way that parents can take in educating children as an embodiment of asense of responsibility to children. The factors that influence parenting stylesare: age, education and socioeconomic level or parent's occupation. This studyaims to determine the description of parenting patterns of working parentsduring the COVID- 19 pandemic in Selebung Village, Keruak District, EastLombok Regency. This study uses a quantitative descriptive method with a crosssectional approach. The population is 2,776 working parents and 97 people areused as samples. The results showed that the type of parenting applied by therespondents was democratic parenting as many as 62 people (63.9%),authoritarian 13 people (13.4%) and permissive 22 people (22.7%). It is hopedthat parents can spend time with their children, can build communication withchildren and parents can provide explanations related to covid-19 and forfurther researchers it is hoped that they can examine other factors regardingparenting patterns during the covid-19 pandemic.